Predicting and exploring network components involved in pathogenesis in the malaria parasite via novel subnetwork alignments. Issue 4 (December 2015) - Cai, Hong; Lilburn, Timothy; Hong, Changjin; Gu, Jianying; Kuang, Rui; Wang, Yufeng
Abstract Background Malaria is a major health threat, affecting over 40% of the world's population. The latest report released by the World Health Organization estimated about 207 million cases of malaria infection, and about 627, 000 deaths in 2012 alone. During the past decade, new therapeutic targets have been identified and are at various stages of characterization, thanks to the emerging omics-based technologies. However, the mechanism of malaria pathogenesis remains largely unknown. In this paper, we employ a novel neighborhood subnetwork alignment approach to identify network components that are potentially involved in pathogenesis. Results Our module-based subnetwork alignment approach identified 24 functional homologs of pathogenesis-related proteins in the malaria parasiteP. falciparum, using the protein-protein interaction networks inEscherichia coli as references. Eighteen out of these 24 proteins are associated with 418 other proteins that are related to DNA replication, transcriptional regulation, translation, signaling, metabolism, cell cycle regulation, as well as cytoadherence and entry to the host. Conclusions The subnetwork alignments and subsequent protein-protein association network mining predicted a group of malarial proteins that may be involved in parasite development and parasite-host interaction, opening a new systems-level view of parasite pathogenesis and virulence.